2006
DOI: 10.1194/jlr.m500518-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides do not affect ABC transporter function in human neuroblastoma cells

Abstract: Previous studies have indicated a role for glucosylceramide synthase (GCS) in multidrug resistance (MDR), either related to turnover of ceramide (Cer) or generation of gangliosides, which modulate apoptosis and/or the activity of ABC transporters. This study challenges the hypothesis that gangliosides modulate the activity of ABC transporters and was performed in two human neuroblastoma cell lines, expressing either functional P-glycoprotein (Pgp) or multidrug resistance-related protein 1 (MRP1). Two inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Both MRP1 in HT29 col MDR tumour cells and Pgp in 2780AD MDR tumour cells were found to be enriched in membrane domains defined by their insolubility in the non-ionic detergent Lubrol. It was shown previously that inhibition of GCS and hence depletion of glycosphingolipids did not affect MRP1 efflux activity in HT29 col cells [39] or in human neuroblastoma cells [18]. As noted above, other sphingolipids, probably SM and Cer, can compensate for the loss of glycosphingolipids under the conditions of GCS inhibition.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Both MRP1 in HT29 col MDR tumour cells and Pgp in 2780AD MDR tumour cells were found to be enriched in membrane domains defined by their insolubility in the non-ionic detergent Lubrol. It was shown previously that inhibition of GCS and hence depletion of glycosphingolipids did not affect MRP1 efflux activity in HT29 col cells [39] or in human neuroblastoma cells [18]. As noted above, other sphingolipids, probably SM and Cer, can compensate for the loss of glycosphingolipids under the conditions of GCS inhibition.…”
Section: Discussionmentioning
confidence: 74%
“…One study described that gangliosides activate Pgp through modulation of its phosphorylation state [17]. Another study reached the conclusion that gangliosides are not involved in modulation of ABC transporter localization and function [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Using these compounds, glucosylceramide synthase function was dissociated from MDR (59). Moreover, it was shown that both the localization in DRMs and the eOEux function of Pgp and MRP1 were not aŠected in spite of e‹cient depletion of glycolipids in human neuroblastoma cell lines SK-N-FI and SK-N-AS, respectively (60). Taken together, glycolipids in some cells appear to modulate Pgp, but are clearly not essential as they are without eŠect in other tumor cell lines.…”
Section: F Sphingolipidsmentioning
confidence: 86%
“…The MDR phenotype of cells used in this work is well described, being representative of freshly obtained cells from patients with chemotherapy refractory chronic myeloid leukemia (42,43). In spite of data indicating that GlcCer modulates ABCB1 expression (17), and considering the promiscuity and overlap in recognition of substrates (44), the relevance of GSL to ABC activity is controversial at best (45). As such, we observed that sub-toxic GSL depletion was not able to affect the expression of ABCB1 and ABCC1 on neither MDR cell; a 24 h incubation with 2 M EtDO-P4, however, showed reductions in the expression of ABCB1 exclusively.…”
Section: Discussionmentioning
confidence: 99%